Green Accounting for Medium-Sized Enterprises: A Review of Participatory Action Research Towards A Sustainable Future - Rasyid, Sumarsih; Azis, Nur Alimin; Rahmat, Aswar (International Journal of Economics and Financial Issues, 2024)
The growth of medium-sized companies in the last decade has had a significant impact on the environment, especially in Indonesia’s major cities. This research aims to develop an environmental reporting model (green accounting) that is suitable for medium-scale companies. Using a participatory action research (PAR) approach, the research involved stakeholders such as entrepreneurs, government, academics, and environmental activists in formulating this reporting model. The study was conducted in Makassar City with 140 medium-scale companies as respondents. Data was collected through questionnaires, interviews, and observations, followed by focus group discussions (FGDs) to develop the reporting model. The results show that sustainability awareness is quite high, but the implementation of environmentally friendly practices is still limited due to the lack of technical knowledge, resources, and multi-stakeholder involvement, especially from the government. The FGDs formulated three main indicators of environmental reporting: water, energy and waste. This research offers an original contribution by developing an environmental reporting model specifically designed for medium-sized enterprises in developing countries. The reporting model developed in this study can be applied to medium-sized enterprises not only in Indonesia, but also in other countries. Theoretically, the results of this study provide theoretical support for the need for a more in-depth study of sustainability issues in medium-sized companies. However, this study has a weakness in that the research respondents are only half of the population of medium-sized companies in Makassar City, Indonesia.